Always a catch! : how I punched my way into marrying a prince, 5 - Momoyo, Mayo; Mito, Itsuki (Square Enix Manga, 2025)
Maria and Prince Renato's engagement party went off without a hitch--well, besides the part where there was an attack orchestrated by Lord Ireneo's paramour! But that's all taken care of, and now Maria is officially acknowledged as the future princess of Rubini.